2022
DOI: 10.3390/ijms24010701
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potency of Induced Pluripotent Stem-Cell-Derived Corneal Endothelial-like Cells for Corneal Endothelial Dysfunction

Abstract: Corneal endothelial cells (CECs) do not proliferate or recover after illness or injury, resulting in decreased cell density and loss of pump/barrier function. Considering the shortage of donor cornea, it is vital to establish robust methods to generate CECs from induced pluripotent stem cells (iPSCs). We investigated the efficacy and safety of transplantation of iPSC-derived CECs into a corneal endothelial dysfunction (CED) rabbit model. iPSCs were generated from human fibroblasts. We characterized iPSCs by de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Corneal endothelial cells (CECs), which are located at the innermost layer of the cornea and dehydrate the corneal stroma, are different from vascular endothelial cells [ 55 ]. CECs originate from neural crest cells [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Corneal endothelial cells (CECs), which are located at the innermost layer of the cornea and dehydrate the corneal stroma, are different from vascular endothelial cells [ 55 ]. CECs originate from neural crest cells [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Corneal endothelial cells (CECs), which are located at the innermost layer of the cornea and dehydrate the corneal stroma, are different from vascular endothelial cells [ 55 ]. CECs originate from neural crest cells [ 55 ]. TGF-β is a multifunctional cytokine that plays a crucial role in regulating cell growth, differentiation, migration, and survival [ 20 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…This significantly reduces the number and quality of HCECs available for culture [24]. Additionally, compared to cells from young donors, cells from older donors grow more slowly, and exhibit high heterogeneity as well as characteristics of senescence [26]. Also, the proliferative capacity of HCECSs is limited to an average of three-to-four subcultures, beyond which the cells become fibroblastic or senescent [27].…”
Section: Introductionmentioning
confidence: 99%
“…They are typically maintained in a non-proliferative state in vivo but have been shown to proliferate in vitro [ 4 , 14 ]. Numerous groups have reported a variety of cell sources and methods to achieve functional CECs, including deriving CECs from the expansion of primary donor cadaveric CECs [ 15 , 16 , 17 , 18 ], human embryonic stem cells (hESC) [ 19 , 20 , 21 , 22 ] and human induced pluripotent stem cells (hiPSC) [ 23 , 24 , 25 ]. Ong et al also recently reported functional outcomes with an alternative method that did not require complex cellular propagation techniques.…”
Section: Introductionmentioning
confidence: 99%